2018
DOI: 10.1371/journal.pone.0191359
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Thalamic Deep Brain Stimulation on speech dynamics in patients with Essential Tremor: An articulographic study

Abstract: Acoustic studies have revealed that patients with Essential Tremor treated with thalamic Deep Brain Stimulation (DBS) may suffer from speech deterioration in terms of imprecise oral articulation and reduced voicing control. Based on the acoustic signal one cannot infer, however, whether this deterioration is due to a general slowing down of the speech motor system (e.g., a target undershoot of a desired articulatory goal resulting from being too slow) or disturbed coordination (e.g., a target undershoot caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 58 publications
7
42
1
Order By: Relevance
“…For this study we recorded natural sentence production of nine ET patients who underwent a DBS surgery. A subset of the same recording session for fast syllable repetition tasks is published in Mücke et al (2018). For our cohort, a tremor reduction of 64.13% was observed after the surgery (detailed information provided in Table 1).…”
Section: Participants and Recordingsmentioning
confidence: 99%
See 4 more Smart Citations
“…For this study we recorded natural sentence production of nine ET patients who underwent a DBS surgery. A subset of the same recording session for fast syllable repetition tasks is published in Mücke et al (2018). For our cohort, a tremor reduction of 64.13% was observed after the surgery (detailed information provided in Table 1).…”
Section: Participants and Recordingsmentioning
confidence: 99%
“…When medication fails or is not tolerated by the patient, chronic deep brain stimulation (DBS) of the nucleus ventralis intermedius (VIM) of the thalamus (Flora, Perera, Cameron, & Maddern, 2010) or the posterior subthalamic area (PSA) ( Barbe et al, 2018) has been shown to be an effective treatment option (see Figure 2). While tremor suppression may reach values of over 90%, some patients report that DBS has a deleterious effect on their speech production, thus impacting their quality of life and social functioning (Flora et al, 2010;Barbe et al, 2014;Mücke et al, 2018). So far, only a few studies have investigated the stimulation-induced deterioration in speech.…”
Section: Speech Motor Control In Essential Tremor Patients Treated Wimentioning
confidence: 99%
See 3 more Smart Citations